The 3-modular characters of the Rudvalis sporadic simple group and its covering croup - Hiss, Gerhard (Mathematics of computation, 1994)
The decomposition numbers of the Rudvalis sporadic simple group and of its double covering group modulo 3 are completely determined. The results were obtained using the computer algebra system MOC developed by Jansen, Lux, Parker, and the author, but the proofs are given in conventional form and can be verified by hand with the ordinary character table.